An empirical investigation of term structure and economic activity in Turkey - Erarslan, Nazan (My University, 2005)
This thesis investigates the explanatory power of the term structure for the industrial production growth during Feb.1994-Nov.2004 in Turkey. Least squares estimation technique and probit modelling methodologies are used for this purpose. There are three major findings. First of all, both models indicate that there is a significant relationship between the slope of the interest rate curve and the growth of production. A narrowing spread is found to mean the production growth is increasing in least squares estimations. Secondly, the recession in 1994 is detected with about 60% probability, the recession in 1999 is detected with about 50% probability and the recession in 2001 is not detected since it is a structrual break with the spread in probit results. However, the movements of the production growth can not be predicted before more than one or two months and the explanatory power of the spread is found lower than the studies done in developed countries. Moreover, the monetary policy stance is found as an important factor in Turkey for the spread to contain valuable information about the future and current conditions of the economy. In the period 1998-2000 which has a determined anti-inflationary policy with exchange rate targeting, spread performs better than the other periods. Deepening and liberalization of the financial market and improvement in the debt conditions of the economy will increase the predictive power of the spread in the future.

Bu tez Şub.1994-Kas.2004 döneminde Tükiye'deki vade yapısının sanayi büyüme endeksinin büyümesi için açıklayıcı gücünü araştırmaktadır. Bu amaçla least squares ve probit modelleme teknikleri kullanılmıştır. Üç ana bulgu vardır. İlk olarak, iki model de vade farkı ile sanayi büyüme endeksinin büyümesi arasındaki ilişkinin önemli olduğunu göstermiştir. Least squares sonuçlarına göre daralan vade farkının üretimdeki büyümenin arttığını gösterdiği bulunmuştur. Buna ek olarak, probit sonuçlarına göre 1994 yılındaki kriz dönemi yaklaşık %60 ihtimalle, 1999 yılındaki kriz dönemi yaklaşık %50 ihtimalle tahmin edilmiş fakat 2001 yılındaki kriz dönemi yapısal bir kırılma olması dolayısıyla tahmin edilememiştir. Ayrıca, sanayi büyüme endeksinin hareketleri bir yada iki aydan daha fazla öncesinden tahmin edilememiş ve vade yapısının açıklayıcı gücü gelişmiş ülkelerde yapılan benzer çalışmalara göre daha düşük çıkmıştır. Son olarak, Türkiye'deki vade yapısının ekonominin gelecekteki ve şu andaki durumu ile ilgili değerli bir bilgi verebilmesi için para politikasının durumunun önemli olduğu sonucuna varılmıştır. Kararlı bir anti-enflasyonist politika ile kur hedeflemesi yapılan 1998-2000 yılları arasında, vade farkı diğer dönemlere göre daha iyi bir performans göstermiştir. Türkiye'deki finansal marketin derinleşmesi ve liberalleşmesiyle birlikte, ekonominin borç durumunun iyileşmesi vade yapısının gelecekteki tahmin ve açıklayıcı gücünü arttıracaktır.
Keywords: Ekonomi Politikası_Türkiye; Ekonomik Gelişim_Türkiye; Türkiye_Ekonomik Durum